Embracing the Chaos: Alloying Adds Stochasticity to Twin Embryo Growth - Hu, Yang; Turlo, Vladyslav; Beyerlein, Irene J; Mahajan, Subhash; Lavernia, Enrique J; Schoenung, Julie M; Rupert, Timothy J (Physical review letters, 2020)
High-throughput atomistic simulations reveal the unique effect of solute atoms on twin variant selection in Mg-Al alloys. Twin embryo growth first undergoes a stochastic incubation stage when embryos choose which twin variant to adopt, and then a deterministic growth stage when embryos expand without changing the selected twin variant. An increase in Al composition promotes the stochastic incubation behavior on the atomic level due to nucleation and pinning of interfacial disconnections. At compositions above a critical value, disconnection pinning results in multiple twin variant selection.